# Simplify this equation: 25-a^2 / 3a^2-13a-10

### 1 Answer | Add Yours

We can factor the top using Difference of Two Squares.

`x^2 - y^2 = (x - y)(x + y)`

`25 - a^2 = (5 - a)(5 + a)`

For the bottom, we can use ac method.

First, identify a, b, and c.

a = 3, b = -13 and c = -10.

Multiply a and c. 3 * -10 = -30.

We will find two numbers which when we multiply we get -30 (value of ac), and when we add we get -13 (value of b).

We can first lists the pair factors of -30 and their sum.

-30 and 1 : -30 + 1 = -29

-10 and 3: -10 + 3 = -7

-6 and 5: -6 + 5 = -1.

-15 and 2: -15 + 2 = -13.

Hence, the numbers we are looking for are -15 and 2. We will use those numbers to rewrite the middle term.

`3a^2 - 15a + 2a - 10`

We can split the terms into two groups.

`(3a^2 -15a) + (2a - 10)`

Factor out the gcf from each group.

` ` `3a(a - 5) + 2(a - 5)`

Factor out the common factor.

`(a - 5)(3a + 2)`

We can factor out a -1 from a - 5.

`-(-a + 5)(3a + 2) = -(5 - a)(3a + 2)`

So, our rational expression will be:

`((5 - a)(5 + a))/(-(5 - a)(3a + 2))`

Cancel common factor on top and bottom.

So, the answer will be: **-(a + 5)/(3a + 2)** .